O que pode o gênero no cinema? Efeitos deformativos no currículo escolar - Silva, Rafael Lesses da (2023)
This research scribbles, deforms and waves to the insurgencies of the body in the face of alternatives composed of the triad of gender, cinema and Deformation that weave together with this writing the following problem: what are the ways of thinking about teacher deformation as an educational policy crossed by cinema and by questions of gender and sexuality? A guiding question that will be diluted in relation to the following objectives: to analyze discourses about the potential of gender and sexuality studies in education; understand the ways in which cinema relates and activates the performativities of bodies; to produce a Cinematographic Curatorial Portfolio that points to corporeal experimentation and provides alternatives for access to the cinema, being able to re/create its effects in the school and in the teacher's deformation; make the notion of deformation work as a political strategy for revising, deconstructing and transgressing practices and existences in teaching. That said, it should be noted that the DEformative notion operated in this dissertation writing from the methodological camera of sociopoetics, which triggers the bodies involved in the research process, considers their cultural, social, political knowledge and other experiences with the world, that is, recognizes that research is not solitary, suspended from relationships with participants. Tensioning the notion of Deformation is perhaps a (RE)thinking of what we choose as “truth” and fabricating other possibilities is to put oneself back on the path of the unknown and be willing to intend “knowledge” in the midst of the discursive game of cinema and gender. Thus, it is concluded that the teacher's deformation echoed at various times between the lines of this writing, legitimizing the active bodies of teachers. To speak of deformation is to extend beyond bodies, to overflow and blur a curricular culture that permeates the school terrain; to deform is to doubt yourself, your conceptions and truths; it is to envision other possibilities that allow us to look at what is different. With that, cinema can be an interesting device in this endeavor. After all, what of me does art-cinema trigger from myself?